2017
DOI: 10.1089/lrb.2016.0026
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Drainage During Wound Healing in a Hindlimb Lymphedema Mouse Model

Abstract: In a hindlimb lymphedema mouse model, lymph transiently accumulated in subcutaneous tissue, and then was gradually absorbed by the existing lymph vessels. The increase in the number of lymph vessels contributes to lymph drainage during wound healing. Acute lymphedema because of transient lymphatic dysfunction has little effect on wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Lymphatics were visualized using the NIRF imaging system (Pde-neo; Hamamatsu Photonics K.K., Shizuoka, Japan) after anesthetization with 1.5% isoflurane. Pde-neo emitted light at 760 nm and detected light at wavelengths greater than 820 nm, and, thus, detected ICG flow because ICG has an excitation wavelength of 805 nm and emission wavelength of 840 nm 18 , 32 . After an injection of 2 to 10 μl ICG, we massaged the injection site using absorbent cotton wool to promote ICG absorbance.…”
Section: Methodsmentioning
confidence: 99%
“…Lymphatics were visualized using the NIRF imaging system (Pde-neo; Hamamatsu Photonics K.K., Shizuoka, Japan) after anesthetization with 1.5% isoflurane. Pde-neo emitted light at 760 nm and detected light at wavelengths greater than 820 nm, and, thus, detected ICG flow because ICG has an excitation wavelength of 805 nm and emission wavelength of 840 nm 18 , 32 . After an injection of 2 to 10 μl ICG, we massaged the injection site using absorbent cotton wool to promote ICG absorbance.…”
Section: Methodsmentioning
confidence: 99%
“…The observation protocol for lymphography has previously been described [20]. In the mice that were anesthetized using 1.75% isoflurane inhalation, we injected 2 μl ICG (2.5 mg/ml) into the hindlimb to investigate the lymph flow after lymphatic ligation.…”
Section: Observation Of Icg Lymphographymentioning
confidence: 99%
“…When collateral LVs bridging the distal LV (over the area of lymphadenectomy) to the proximal LV or to the remaining LNs with LVs are observed in patients using lymphoscintigraphy (at the area of the lymphadenectomy), lymphedema is said to be mild or moderate [3,5,7,[10][11][12]. Moreover, animal studies involving canines, rabbits, rats, and mice have previously reported that similar collateral LVs (also known as lymphatic detours) develop following LN dissection alone or in combination with LVs [13][14][15][16][17][18][19][20][21][22]. Collateral LVs in rodents have been detected using indocyanine green (ICG) in 2 days [22], in 3 days [20], in 1 week [14,15] and in 10 days [21] after lymphadenectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphedema is known to delay wound healing. [1][2][3][4] If water and macromolecules are not cleared from the inter-stitium, the oncotic and hydrostatic pressure balance within the tissues is altered, and cell damage results contributing further to delayed wound healing. 5 In addition to these pathophysiological mechanisms, it is suspected that the balance of immune cells involved in wound healing is disrupted in lymphedema.…”
Section: Introductionmentioning
confidence: 99%